2009
DOI: 10.1111/j.1365-2648.2008.04875.x
|View full text |Cite
|
Sign up to set email alerts
|

The quality of paediatric nursing care: developing the Child Care Quality at Hospital instrument for children

Abstract: The CCQH questionnaire is a promising instrument for use among children. Future research is needed to evaluate its suitability for completion by children of varying ages and in different cultures and healthcare settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
(99 reference statements)
0
28
0
6
Order By: Relevance
“…On the basis of previous studies carried out by the authors of the CCQH (Pelander, Lehtonen et al, ; Pelander, Leino‐Kilpi et al, ; Pelander et al., ), in our sample we considered a wide age range of children. It is obvious that it was easier for older children to answer the questionnaire; however, as confirmed by our empirical data and according to previous research (Pelander et al., ; Rebok et al., ), we observed that the use of both words and graphic representations as response options yielded good results, and even the youngest participants, with fewer languages skills, were able to express their own points of view. Children can be actively involved in research in health care to a larger extent than is currently seen, for example, if the methods used are adapted to facilitate taking a child's perspective (Nilsson et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of previous studies carried out by the authors of the CCQH (Pelander, Lehtonen et al, ; Pelander, Leino‐Kilpi et al, ; Pelander et al., ), in our sample we considered a wide age range of children. It is obvious that it was easier for older children to answer the questionnaire; however, as confirmed by our empirical data and according to previous research (Pelander et al., ; Rebok et al., ), we observed that the use of both words and graphic representations as response options yielded good results, and even the youngest participants, with fewer languages skills, were able to express their own points of view. Children can be actively involved in research in health care to a larger extent than is currently seen, for example, if the methods used are adapted to facilitate taking a child's perspective (Nilsson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have tested the psychometric proprieties of the CCQH instrument in pediatric settings, demonstrating the validity and reliability of the questionnaire (Pelander, ; Pelander et al., ). The CCQH questionnaire is the only validated instrument specifically designed to measure the quality of pediatric nursing from children's points of view (Pelander & Leino‐Kilpi, ; Pelander, Leino‐Kilpi et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children's own views should be considered in the planning and delivery of paediatric care. For example, the Child Care Quality at Hospital has been shown to be useful among children during hospital stays [26], and in a study by Stewart et al . [27], children were used as experts and as content validity evaluators for a child self‐report instrument, the Uncertainty Scale for Kids.…”
Section: Introductionmentioning
confidence: 99%
“…; Pelander et al . ). Children and adolescents are perfectly able to give their own opinions about their health care, if they are given the right opportunity to do so.…”
Section: Introductionmentioning
confidence: 97%